Napier grass (Pennisetum purpureum Schum) management strategies for dairy and meat production in the tropics and subtropics: yield and nutritive value - Islam, M. Rafiq; Garcia, Sergio C.; Sarker, Nathu R.; Islam, Md. Ashraful; Clark, Cameron E. F. (Frontiers in Plant Science, 2023)
Napier grass (Pennisetum purpureum Schumach) comprises up to 80% of the cattle diet in many tropical and subtropical regions and is used primarily by smallholder farmers. Despite the grasses high yield, resulting animal productivity from this grass is low. One of the key reasons for low animal productivity from Napier grass is its low nutritive value under current management. Taken together, previous work has shown the current yield, crude protein (CP) and metabolisable energy (ME) of Napier grass to be 26 t dry matter (DM)/ha/yr, 96 g/kg DM and 8.7 MJ/kg DM, respectively ranging from 2 to 86 t DM/ha/yr, 9-257 g CP /kg DM and 5.9-10.8 MJ ME /kg DM suggesting opportunity for significant improvement on both yield and nutritive value of this grass. The DM yield and nutritive value of this grass inversely related indicating a trade-off between yield and quality, however, this trade off could be minimised by increasing sowing density and harvesting frequency. Available literature shows that this simple management strategy of increasing sowing density (50 cm x 40 cm) and harvesting frequency (11-12 harvests/year) provides 71 t DM/ha with 135 g/kg DM CP and 10.8 MJ ME/kg DM. This quality of Napier grass has the potential to increase both milk and meat production substantially in the tropics and subtropics and farmers acceptance of this simple management likely to be acceptable due to the high yield obtained through these management. However, there is a paucity of work in this field. Therefore, management strategies to improve the nutritive value of Napier grass are required for further increase in milk and meat production in the tropics and subtropics to improve food security of more than half of the global population living in these regions.